Investor Behavior Under Uncertainty: Sentiment and Herding ‎Across Market Phases - Ninan, Dr.Minnie Mary; Abraham , Dr.Ann; Francis, Ashly (International Journal of Accounting and Economics Studies, 2025)
Behavioral finance argues that investing behavior is influenced by emotions, biases, and ‎cognitive ability (Almansour & Arabyat, 2017). The impact of behavioral shifts in investing has ‎gained prominence in recent years. The COVID-19 pandemic sent waves of uncertainty to all ‎spheres of life, even to the economic one. This study intends to examine the presence of herding ‎behavior and investor sentiments in the Indian Stock Market, focusing on the benchmark index ‎of Nifty 50. The impact was analyzed by focusing on three different phases, namely the pre-COVID phase, the crisis, and the post, COVID i.e. the recovery phase. Quantitative techniques ‎were employed to measure the presence of investor sentiment and to detect herding patterns in ‎the stock market. The results reveal significant behavioral shifts across the three phases, offering ‎insights into sentimental investment decisions under crisis conditions. These findings hold ‎relevance for market participants, policymakers, and researchers interested in behavioral finance‎.